Administrative Reform in Indonesia: How Far is The Citizens Online Complaints-Handling System (LAPOR!) About to Reach The Open Government Agenda? - Dilani Maryam; Adi Nurul Hadi; Ria Putri Palupijati (Jurnal Administrasi dan Kebijakan Publik, 2018)
Indonesia is one of the most prominent countries that have a strong interest in implementing open government agendas. In 2011, the Indonesian government along with seven other country leaders took the initiative to form a global network movement called Open Government Partnership (OGP) as a platform in making their governments more open, accountable, and responsive to citizens. To connect the international agendas with national bureaucratic reforms agenda, the Indonesian government also establish the movement called Open Government Indonesia (OGI). Under the national public complaints management system, LAPOR! was established as the flagship of the open government movement to encourage a "no wrong door policy" guaranteeing the right of the people to file any complaint to be channeled to the authorized public service provider. The purpose of this paper is to assess how far the LAPOR! is being implemented to support open government agenda. The topic will be analyzed using Governance approach, given that Open Government movement is a new and more efficient way of doing governance. Three main dimensions will be the main focus of the discussion, namely; public participation, collaboration, and transparency. This research is conducted by using a qualitative descriptive method. Data are collected through official documents or publications, and other various written sources including journals, news, articles related to the topic of discussion. The findings of this research reveal that the implementation of LAPOR! is still facing challenges. There are still some challenges that need to be addressed.